2016
DOI: 10.1088/0026-1394/53/2/s55
|View full text |Cite
|
Sign up to set email alerts
|

When the model doesn’t cover reality: examples from radionuclide metrology

Abstract: It could be argued that activity measurements of radioactive substances should be under statistical control, considering that the measurand is unambiguously defined, the radioactive decay processes are theoretically well understood and the measurement function can be derived from physical principles. However, comparisons invariably show a level of discrepancy among activity standardisation results that exceeds expectation from uncertainty evaluations. Also decay characteristics of radionuclides determined from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Although science is always open to new ideas, the power of the argument lies in the quality of the empirical test. Good metrology entails a detailed understanding of the uncertainty budget [70], and good communication thereof. The conclusions of Lindstrom [71] with respect to the roles of the authors, reviewers and editors of scientific journals remain essential for producing believable science.…”
Section: Discussionmentioning
confidence: 99%
“…Although science is always open to new ideas, the power of the argument lies in the quality of the empirical test. Good metrology entails a detailed understanding of the uncertainty budget [70], and good communication thereof. The conclusions of Lindstrom [71] with respect to the roles of the authors, reviewers and editors of scientific journals remain essential for producing believable science.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental uncertainties used in these measurements are discussed in Refs. [14,15]. The exact total duration of this dataset is 7.83 years and the median sampling interval is 0.00279 years or approximately 1 day.…”
Section: A Bnl and Ptb Datasetsmentioning
confidence: 99%
“…These results were rebutted by Pomme et al [1], who found no evidence for periodicities in the decay rates of 36 Cl using more accurate measurements at Physikalisch-Technische Bunde-sanstalt Braunschweig (PTB), obtained using the tripleto-double coincidence ratio measurement techniques [6]. Pomme [14,15] has also raised concerns about the detector stability and control of experimental uncertainties in the BNL measurements, which are now more than three decades old. Furthermore, the invariability of the decay constants for 36 Cl was also demonstrated using tripleto-double coincidence ratio measurements [16], to refute claims of oscillations ascribed to the changes in Earth-Sun distance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they observed a prominent 'transient cycle' of 12.7 a −1 (28.76 days period, 0.07% amplitude) in spectrograms formed from countings of 36 Cl and 32 Si decays in a gasflow proportional counter at BNL (Alburger, Harbottle, and Norton, 1986) and found them indicative of the synodic rotation rate of the radiative zone of the Sun, since it matches its helioseismologically determined period of 28.7 days (Schou et al, 1998;Komm et al, 2003). However, it is questionable whether all experimental uncertainties were under control in the aforementioned 36 Cl and 32 Si decay measurements (Pommé, 2015(Pommé, , 2016. Scargle (2016, 2017) also linked the 12.7 a −1 period with an insignificantly small oscillation in the Super-Kamiokande (SK-I) (Yoo et al, 2003) neutrino flux measurements and concluded that modulations in 'neutrino-induced' beta decays can provide information about the deep solar interior.…”
Section: Introductionmentioning
confidence: 98%